2022
DOI: 10.3389/fcvm.2022.984472
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress: An essential factor in the process of arteriovenous fistula failure

Abstract: For more than half a century, arteriovenous fistula (AVFs) has been recognized as a lifeline for patients requiring hemodialysis (HD). With its higher long-term patency rate and lower probability of complications, AVF is strongly recommended by guidelines in different areas as the first choice for vascular access for HD patients, and its proportion of application is gradually increasing. Despite technological improvements and advances in the standards of postoperative care, many deficiencies are still encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 250 publications
0
8
0
Order By: Relevance
“…Oxidative stress plays an important role in heart failure, including ACF. The increased synthesis and secretion of ROS leads to a disturbance of the oxidative balance, which in turn stimulates many signaling pathways that regulate various processes, including the promotion of cell proliferation and migration and the secretion of ECM [ 19 ]. The levels of TBARS, as a marker of oxidative stress, decreased in the left ventricle in the TGR(A1-7)3292 group compared to the HSD ACF group and in the right ventricle, and also in the TGR(A1-7)3292 group, but compared to the TGR ACF group ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress plays an important role in heart failure, including ACF. The increased synthesis and secretion of ROS leads to a disturbance of the oxidative balance, which in turn stimulates many signaling pathways that regulate various processes, including the promotion of cell proliferation and migration and the secretion of ECM [ 19 ]. The levels of TBARS, as a marker of oxidative stress, decreased in the left ventricle in the TGR(A1-7)3292 group compared to the HSD ACF group and in the right ventricle, and also in the TGR(A1-7)3292 group, but compared to the TGR ACF group ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, AGEs bind to RAGE and induce reactive oxygen species (ROS) production through activation of NADPH oxidase and NF-κB signaling pathways. Reactive oxygen species (ROS) have been shown to cause smooth muscle proliferation and intimal hyperplasia [ 10 , 59 ]. Therefore, blocking the AGE-RAGE signaling pathway may have great potential significance for the treatment of AVF failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although these factors show considerable differences between different regions and populations, an increasing number of basic studies have revealed common molecular mechanisms that mediate AVF failure [ 9 ]. Invasive intimal hyperplasia is the most important cause of AVF failure and is histologically characterized by constriction of the lumen and function of the outflow tract caused by the accumulation of large numbers of contractile smooth muscle cells, fibroblasts, immune cells, and extracellular matrix [ 1 , 10 , 11 ]. The occurrence of intimal hyperplasia is closely related to biological pathways such as inflammation, hypoxia, oxidative stress, and shear stress [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with complications and treatment related to vascular access account for nearly one-third of HD admissions ( 2 ). One main reason for AVF maturation failure is insufficient outward remodeling, which fails to adapt to changes in hemodynamics following arterialization ( 7 ). Another reason is excessive neointimal hyperplasia (NIH) within the fistula and thrombosis at the anastomosis, leading to luminal stenosis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…An establishment of a good animal model to reproduce this particular pathophysiology is key to the rigour and success of subsequent studies. It was shown that multiple vascular biological pathways may be involved in causing the development of this pathologic change, including inflammation, oxidative stress, hypoxia, and altered hemodynamics ( 7 ). Large animals are anatomically and physically closer to human and can effectively demonstrate hemodynamic changes, which is a limitation of small animals.…”
Section: Introductionmentioning
confidence: 99%